2020
DOI: 10.3390/ijerph17134846
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ambient Air Pollution on Hospital Readmissions among the Pediatric Asthma Patient Population in South Texas: A Case-Crossover Study

Abstract: Few studies have evaluated the association between ambient air pollution and hospital readmissions among children with asthma, especially in low-income communities. This study examined the short-term effects of ambient air pollutants on hospital readmissions for pediatric asthma in South Texas. A time-stratified case-crossover study was conducted using the hospitalization data from a children’s hospital and the air pollution data, including particulate matter 2.5 (PM2.5) and ozone concentrations, from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 45 publications
(66 reference statements)
0
29
0
Order By: Relevance
“…There were six studies [ 9 , 10 , 11 , 12 , 13 , 22 ] using the odds ratio (OR) to assess the likelihood of readmission rate due to outdoor exposure. Findings for these can be found in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were six studies [ 9 , 10 , 11 , 12 , 13 , 22 ] using the odds ratio (OR) to assess the likelihood of readmission rate due to outdoor exposure. Findings for these can be found in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Baek et al (2020) [ 12 ] used seasonal trends; however, they also looked at the effects of air pollutants, particulate matter 2.5 (PM 2.5 ), and ozone (O 3 ). The seasons were divided into a warm season, defined as the months between May and October, or cold season, defined as the months between November and April.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, studies have confirmed that PM 2.5 is the only compound that is independently related to emergency department visits for asthma patients [56,57]. Moreover, a case-crossing study from South Texas has shown that elevated PM 2.5 concentration increased the risk of readmissions in children with asthma [58]. Wheezing is a primary respiratory symptom to assess exogenous factors that trigger asthma attacks.…”
Section: Asthmamentioning
confidence: 99%